Essential Oils-Loaded Electrospun Biopolymers: A Future Perspective for Active Food Packaging - Shahla Ataei; Pedram Azari; Aziz Hassan; Belinda Pingguan-Murphy; Rosiyah Yahya; Farina Muhamad (Advances in Polymer Technology)
The growth of global food demand combined with the increased appeal to access different foods from every corner of the globe is forcing the food industry to look for alternative technologies to increase the shelf life. Essential oils (EOs) as naturally occurring functional ingredients have shown great prospects in active food packaging. EOs can inhibit the growth of superficial food pathogens, modify nutritious values without affecting the sensory qualities of food, and prolong the shelf life when used in food packaging as an active ingredient. Since 2016, various reports have demonstrated that combinations of electrospun fibers and encapsulated EOs could offer promising results when used as food packaging. Such electrospun platforms have encapsulated either pure EOs or their complexation with other antibacterial agents to prolong the shelf life of food products through sustained release of active ingredients. This paper presents a comprehensive review of the essential oil-loaded electrospun fibers that have been applied as active food packaging material.